Unraveling the Right of Return - Friedman, Adina (Refuge: Canada’s Journal on Refugees, 2003)
The notion of Return in many ways epitomizes the Israeli-Palestinian conflict. The Palestinian Right of Return, one embodiment of this notion, has constituted a hurdle in the parties’ attempts to reach a sustainable agreement. Rather than regard the conflict as of zero-sum nature, this paper assumes that Palestinians and Israelis, in their negotiations on the Right of Return and other issues, do not hear each other, and in fact are seldom speaking the same language even when it seems they are discussing the same issue. It examines the ways in which Israelis and Palestinians understand the issue of Return, and suggests a number of factors that influence their different understandings – as well as what each is able to hear from the other. A sustainable agreement would have to take these factors into account in its formulation and in the way in which it is delivered to both peoples.